Some Brief Remarks on Teaching Amharic: A Personal View - Bausi, Alessandro (Aethiopica, 2019)
This article offers a brief comparative view of the teaching of Amharic in the last decades at two major European universities: the Università degli Studi di Napoli “L’Orientale” and the Universität Hamburg. The aim of this brief history is to highlight the severe consequences on the teaching of Amharic enforced by measures set in motion by the Bologna Process since 1999. This changed framework requires adequate strategies and counter-measures in order to safeguard the quality of education and the continuity of our research traditions.